Evaluation of the relationships between floristic heterogeneity of Panicum prionitis Ness tall grasslands and the fire history, hydrological regime and soil texture in the Paraná River floodplain, Argentina - Marchetti, Zuleica Yael (2011)
Tall grassland landscapes in the Paraná River floodplain are associated with a particular natural fluctuation, and to anthropic disturbances that determine their floristic assemblages. This paper addresses tall-grasslands of Panicum prionitis and evaluates the relationship between its floristic composition and the occurrence of fire, hydrological pulses and soil texture. Fifty-eight plots of tall grasslands of 25m2 each were analyzed in eight patches; abundance-cover of each species was recorded. Of the plots, 15 were distributed in three of the eight patches. The three patches had different fire histories: 7 months, 4 years and 14 years from the last fire event. In the eight patches, sediment samples of 0-20cm depth were collected and 20 topographic readings were performed. Vegetation was analyzed by applying classification and indirect ordination multivariate techniques. One hundred and eighteen species distributed in four floristic groups were found. No statistically significant differences in diversity and floristic composition were identified among tall grasslands with different fire history. Differentiation in floristic groups was mainly associated with hydrological pulses and soil texture. Fire does not generate significant changes in species richness, diversity or structure in Panicum prionitis tall grasslands. From the conservation perspective, we believe it is appropriate to suggest that to maintain the permanence of the Panicum prionitis tall grasslands the fire events should not be avoided.